Pengaruh Motivasi Kerja, Kompetensi dan Kompensasi terhadap Kinerja Agen melalui Kepuasan Kerja: Studi pada Prudential Life Assurance di Makassar - Muhammad Ikhsan; Andi Reni; Wardhani Hakim (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
The purpose of this study was to determine the effect of work motivation, competence and compensation on agent performance through job satisfaction at Prudential Life Assurance, and to see whether job satisfaction acts as an intervening variable. The population of this study is a Prudential Life Assurance agent consisting of 8 branch offices in Makassar with a total sample of 90 agents. Data collection is done through questionnaires using simple random techniques. The collected data is then analyzed using the Structural Equation Model (SEM) with PLS 2.0 as a data processing software. From the results of this study found: (1) work motivation has a non-significant effect on job satisfaction but has a significant effect on agent performance, (2) competence has a significant influence on job satisfaction and agent performance, (3) compensation has a significant effect on job satisfaction and agent performance, (4) job satisfaction has no significant effect on agent performance, (5) work motivation, competence and compensation have no significant effect on agent performance through job satisfaction as an intervening variable.